DIVORCE OF CIVIL SERVANTS WITHOUT SUPERIOR PERMISSION IN MASLAHA ANALYSIS - Hari Widiyanto; Muhajir Muhajir (fakultas hukum universitas PGRI Semarang, 2023)
This study discusses the divorce of Civil Servants without the permission of superiors in the analysis of Maslaha (case study of decision No. 678/pdt.g/2021/PA.Wsb in the Wonosobo Religious Court) which aims to answer the problem of: (1) What is the judge's consideration in deciding a civil servant divorce case without the superior's permission at the Wonosobo Religious Court? and (2) How is the analysis of Maslaha in the determination of case number 678/pdt.g/2021/Pa.Wsb. The method used is a field study. The data sources used are primary data sources, namely sources obtained directly from the Wonosobo religious court. And secondary data sources are sources of data obtained from books, documents related to research. The method used is the interview method by applying the interview. The results of the study concluded that: (1) Judge's considerations in deciding case number: 678/pdt.g/2021/Pa.Wsb. regarding the divorce of civil servants without the superior's permission by the Wonosobo Religious Court, the court granted the plaintiff's claim. Dismissed the divorce of one ba'in sughra of the defendant (defendant) against the plaintiff (plaintiff). Even without a letter of permission from superiors, on a warning from the judge, the applicant has stated that he is ready to bear all the risks that have been made according to the certificate dated April 13, 2021. (2) Analysis of Maslaha in case determination number 678/pdt.g/2021/Pa.Wsb . This is in accordance with legal norms and does not conflict with syara' which is the basis for proceedings at the Wonosobo Religious Court.